Choice of the functional monomer of molecularly imprinted polymers: Does it rely on strong acid-base or hydrogen bonding interactions? - Boukadida, Merymene; Anene, Amira; Jaoued-Grayaa, Najeh; Chevalier, Yves; Hbaieb, Souhaira (Colloid and interface science communications, 2022)
The choice of the functional monomer is a key point in the design of molecularly imprinted polymers (MIPs) because its directional interactions with template molecules are required to form molecular imprints acting as selective recognition sites for adsorption. Methacrylic acid (MAA) has very often been employed as a functional monomer for imprinting basic template molecules. Strong acid-base interactions lead to H+ transfer and weak hydrogen bonding between the products of the acid-base reaction. The weakly acidic acrylamide (AA) has shown stronger hydrogen-bonding interactions with histamine (HA) than MAA. Interactions between HA and the functional monomers have been investigated by means of 1H NMR spectroscopy yielding the stoichiometry and complexation constants of their complex species. Adsorption isotherms of HA to both MAA- and AA-based MIPs and their modeling showed a higher selective binding of HA to the AA-based MIP. [Display omitted] •Hydrogen bonding interactions between monomer and template yield selective molecular imprinted materials.•Strong acid-base interactions between monomer and template cause H+ transfer instead of directional interactions.•Acrylamide yields more selective recognition of basic amines than methacrylic acid.